If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -3y = -6 Solving 12 + -3y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -3y = -6 + -12 Combine like terms: 12 + -12 = 0 0 + -3y = -6 + -12 -3y = -6 + -12 Combine like terms: -6 + -12 = -18 -3y = -18 Divide each side by '-3'. y = 6 Simplifying y = 6
| 7.5+(1/2)x=30 | | x+4/5 | | x-5/2 | | x-5/2=x+4/5 | | (51)(40/60)=(54)(x/60) | | -5=-2.5x+10 | | 750-50x= | | -185+35x= | | -1(x)=-x*x-x+5 | | 2x-7=6x+8 | | 7(x-1)+2(3-x)=8 | | 7x+1=8x-12 | | y^2+4y=(9/2) | | 5=0.5x+6 | | (2p+3r)(p-6r)= | | (1/12)x=(1/4)x | | (1/4)x=27 | | (1/12)x=5 | | 5x+3y-x-4y= | | 356t-180=87 | | X^4+x^4= | | 60/5 | | x2/3x=45 | | 1-1/3x=40 | | 16+2x=1-25 | | 8-10x=122-38x | | 9=a/-5 | | 5x^4-36x^2+7=0 | | 6x+7=121-10x | | -4x+4+8x=4x+4 | | -4x+4+8x=4x | | 5+-1=14 |